(untitled) (Bangladesh Journal of Medical Science, 2024)
Objectives Diabetes mellitus (DM) is one of the major chronic non-communicable diseases affecting millions of people worldwide. Diabetic foot ulcers(DFUs) are one of the most important complications of chronic diabetes especially in the elderly population. The aim of this study was to determine the prevalence and associated factors of DFU in adult diabetic patients admitted to Madina Hospital in Mogadishu, Somalia. Materials and Methods The study design was a hospital-based cross-sectional study. Patients admitted to Mogadishu Madina hospital between December 2021 and April 2022 were evaluated. Quantitative data on the prevalence and associated factors of diabetic foot ulcer among adult diabetic patients were used. Results Out of a total of 176 participants, 173 were interviewed, with a response rate of 98.30%. Of the 173 patients, 90 were female (52.02%) and 83 were male (47.98%). Diabetic foot ulcer was detected in 31 of these patients (17.92%). The disease was most common in the 51-60 age group (57.23%). The frequency of DFUs in patients with hypertension was 21/53 (39.62%), and the frequency of diabetic foot ulcers in those who could not control their blood sugar was 29/87 (33.33%). It was observed that 157 (90.75%) of the patients had no diet control and only 16 (3.47%) of them controlled their diets. According to the level of education, DFUs was most common in secondary school level 14 (29.17%). Conclusion DFU is one of the most serious life-threatening consequences of diabetes mellitus. In our study group, the disease was most common in the age range of 51-60 years. Vascular and neurologic changes caused by diabetes mellitus predispose to the development of DFU. Gender difference is not significant in terms of developing the disease. Long disease duration and the presence of hypertension are factors contributing to the development of DFU. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 722-728